2020
DOI: 10.1111/lnc3.12403
|View full text |Cite
|
Sign up to set email alerts
|

How are signed languages learned as second languages?

Abstract: This review addresses the question: How are signed languages learned by adult hearing learners? While there has been much research on second language learners of spoken languages, there has been far less work in signed languages. Comparing sign and spoken second language acquisition allows us to investigate whether learning patterns are general (across the visual and oral modalities) or specific (in only one of the modalities), and hence furthers our understanding of second‐language acquisition (SLA). The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…It would be interesting to consider the challenges they face when the same sign forms occur in their L1 and L2 with different meanings. The L2 learning of sign languages is rarely studied, and the answers to these questions are still incomplete at best (Marshall et al., 2021; Schönström, 2021).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…It would be interesting to consider the challenges they face when the same sign forms occur in their L1 and L2 with different meanings. The L2 learning of sign languages is rarely studied, and the answers to these questions are still incomplete at best (Marshall et al., 2021; Schönström, 2021).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Sometimes, these gestures appear together with speech, cospeech gestures, and sometimes, they are used to complement or replace speech (Özyürek, 2012). Several studies have suggested that such gestural knowledge used in spoken languages can be beneficial for M2 learners' acquisition of sign languages (Casey and Emmorey, 2009;Chen-Pichler and Koulidobrova, 2015;Ortega et al, 2019;Marshall et al, 2021).…”
Section: Sign Second Language Acquisition (Ssla)mentioning
confidence: 99%
“…Previous studies on M2L2 adult learners have shown that they do transfer gestural handshapes in spoken language to sign language (i.e., transfer phonological information), for example, handshape between M1L1 (their spoken first language) and M2L2 (the sign language being learned) (see for example Chen Pichler, 2011;Chen Pichler & Koulidobrova, 2016;Williams & Newman, 2017;Beal, 2020;Marshall, Bel, Gulamani & Morgan, 2020). These handshapes come from gestures that co-occur with spoken language and are different from handshapes in lexical signs, leading to an incorrect production of the lexical sign, i.e., the sign YES in ASL made with "fist" handshape instead of using the S handshape (Chen Pichler & Koulidobrova, 2016).…”
Section: Language Learning (M2l2)mentioning
confidence: 99%